Light up the night - Buchman, M. L. (Matthew Lieber) (Buchman, M. L. (Matthew Lieber). Night stalkers., 2014)
After rescuing Navy SEAL Bill Bruce from his undercover mission in Somalia, hotshot SOAR helicopter pilot Trisha O'Malley, despite their initial animosity, discovers that they must work together to confront their pasts and survive Somalia's pirate lords